EFEKTIVITAS PENEGAKAN HUKUM LINGKUNGAN DALAM MENGATASI KRISIS LINGKUNGAN HIDUP DI INDONESIA - Rahil Khalisa; Saskia Besthianna; Shofa Zahira Arrumaisha; Silviana Cindy Kharissa; Syavina Alya Rohimah (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2025)
The "Effectiveness of Environmental Law Enforcement in Overcoming the Environmental Crisis in Indonesia" will be covered in this article. Deforestation, air and water pollution, and overuse of natural resources are some of the human activities that are contributing to Indonesia's growing environmental crisis. In order to solve this issue, environmental law enforcement is crucial. With an emphasis on the various legal tools used in Indonesia, including the Law on Environmental Protection and Management and administrative, civil, and criminal sanctions, this study examines how well environmental law enforcement has handled the crisis. Thorough research on the application and efficacy of current legal tools is still necessary for certain environmental law enforcement tactics, such as rigorous enforcement and bolstering current environmental regulations. This article employs a normative juridical methodology that includes case studies and a statutory approach. Data is gathered by reviewing relevant literature and analyzing court records pertaining to Indonesian environmental law enforcement. It is anticipated that this research article will help strengthen law enforcement's capabilities and boost public involvement, both of which are essential steps in raising Indonesia's environmental standards.